2021
DOI: 10.1002/acm2.13360
|View full text |Cite
|
Sign up to set email alerts
|

The use of collimator angle optimization and jaw tracking for VMAT‐based single‐isocenter multiple‐target stereotactic radiosurgery for up to six targets in the Varian Eclipse treatment planning system

Abstract: Island blocking occurs in single-isocenter multiple-target (SIMT) stereotactic radiotherapy (SRS) whenever targets share multi-leaf collimator (MLC) leaf pairs. This study investigated the effect on plan quality and delivery, of reducing island blocking through collimator angle optimization (CAO). In addition, the effect of jaw tracking in this context was also investigated. Methods: For CAO, an algorithm was created that selects the collimator angle resulting in the lowest level of island blocking, for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(170 reference statements)
1
3
0
Order By: Relevance
“…These were chosen by the planner using visual assessment of the target locations in the beams-eye-view, resulting in a closer approximation to the optimal solution than using a fixed angle approach. Similar results were reported in a study by Pudsey et al [28] which compared optimized to manually selected collimator angles for VMAT-based single-isocenter multiple-target SRS with a retrospective cohort of 10 patients. They found no significant differences between plans with or without collimator optimization.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These were chosen by the planner using visual assessment of the target locations in the beams-eye-view, resulting in a closer approximation to the optimal solution than using a fixed angle approach. Similar results were reported in a study by Pudsey et al [28] which compared optimized to manually selected collimator angles for VMAT-based single-isocenter multiple-target SRS with a retrospective cohort of 10 patients. They found no significant differences between plans with or without collimator optimization.…”
Section: Discussionsupporting
confidence: 86%
“…Past studies have shown various ways to solve the island-blocking problem and compared to a number of different planning methods [7] , [8] , [22] , [28] . This study shows how beam angle optimization can be clinically implemented using a treatment planning system API to increase efficiency while maintaining plan quality.…”
Section: Discussionmentioning
confidence: 99%
“…A series of SI-VMAT plans for more than five brain metastases generated with 5mm MLCs reported comparatively poor GIs of 5.0 -5.6 ( 51 ). According to Ohira et al, optimization of the collimator angle ( 52 ) can achieve better sparing of healthy brain, although additional jaw tracking did not yield a benefit ( 53 ). The better GIs achieved with the DCA than with VMAT stem from its development as an extension of radiosurgery with conical collimators, but come at the cost of conformity in the case of non-spherical targets ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the previous studies 6 , 7 , 8 , 9 , 10 , 11 , 16 , 17 regarding collimator angle optimization only considered the IB problem and neglected the PG problem. Therefore, in this study, we developed a new collimator angle optimization algorithm that combined the IB and PG areas to fully represent the unnecessary open space area of MLC.…”
Section: Introductionmentioning
confidence: 99%